Quantitative analysis of cementitious materials by X-ray ptychographic nanotomography - Shirani, Shiva; Cuesta-García, Ana María; Gómez-de-la-Torre, María de los Ángeles; Da Silva, Julio C.; Karpov, Dmitry; Díaz, Ana; Holler, Mirko; Trtik, Pavel; García-Aranda, Miguel Ángel (My University, 2021)
Cement manufacturing is responsible for ~7% of the anthropogenic CO2 emissions and hence, decreasing the CO2 footprint, in a sustainable, safe, and cost-effective way, is a top priority. It is also key to develop more durable binders as the estimated world concrete stock is 315 Gt which currently results in ~0.3 Gt/yr of concrete demolition waste (CDW). Moreover, models under development predict a skyrocketing increase of CDW to 20–40 Gt/yr by 2100. This amount could not be easily reprocessed as aggregates for new concretes as such volumes would be more than two times the predicted need. Furthermore, concretes have very complex hierarchical microstructures. The largest components are coarse aggregates with dimensions bigger than a few centimetres and the smallest ones are amorphous components and the calcium silicate hydrate gel with nanoparticle sizes smaller than a few nanometres. To fully understand the properties of current and new cement binders and to optimize their performances, a sound description of their spatially-resolved contents is compulsory. However, there is not a tomographic technique that can cover the spatial range of heterogeneity and features of concretes and mortars. This can only be attained within a multitechnique approach overlapping the spatial scales in order to build an accurate picture of the different microstructural features. Here, we have employed far-field and near-field synchrotron X-ray ptychographic nanotomographies to gain a deeper insight into the submicrometer microstructures of Portland cement binders. With these techniques, the available fields of view range from 40 to 300 um with a true spatial resolution evolving between ~50to~300 nm. It is explicitly acknowledged here that other techniques like X-ray synchrotron microtomography are necessary to develop the whole picture accessing to larger fields of view albeit with poorer spatial resolution and without the quantitativeness in the reconstructed electron densities.
Keywords: Sistemas de imágenes tridimensionales; Rayos X; CO2 footprint; ptychographic nanotomography; X-ray Imaging; Nanotomography